The effect of budesonide and 5-azacytidine on the levels of methylation at the CpG islands of human choline kinase alpha (ckα) and beta (ckβ) promoter - Rahman, Muhammad Al Bunyamin Abdul (2017)
Choline kinase (CK) is the first enzyme in the CDP-choline pathway for the synthesis of phosphotidylcholine, a major component of membrane phospholipid. In human, CK is encoded by ckα and ckβ genes which produce three protein isoforms known as CKα1, CKα2 and CKβ. CKα is involved in tumorigenesis while CKβ is associated with muscular dystrophy. DNA methylation is an important epigenetic mark in gene expression regulation. This study reports on the methylation status of human ckα and ckβ promoter CpG islands after treatment with epigenetic drugs (budesonide and 5-azacytidine). In silico analyses revealed multiple putative CpG islands on each ckα and ckβ promoter through MethPrimer and EMBOSS CpGPlot prediction tools and fifty-nine and sixty-two putative transcription factor binding sites on ckα and ckβ promoter CpG islands respectively through Mat Inspector and TFBIND prediction tools. The methylation status of predicted putative CpG islands were analysed through epigenetic drugs treatment on MCF-7 cell line. Seven regions of out fourteen regions of the promoter CpG islands were successfully amplified by producing PCR products at their expected sizes. These seven regions were targeted for further analysis. MCF-7 were cultured and divided into four groups, consisting of two treatment groups which were budesonide (methylating agent) treated group (70 μM; 24 hours) and 5-azacytidine (demethylating agent)group (1 μM; 96 hours) and two control groups, which were budesonide control group (1% DMSO; 24 hours) and 5-azacytidine control group (1%DMSO; 96 hours). Genomic DNA from all groups was extracted following their respective incubation time with the epigenetic drugs. Fragmentation of the genomic DNA for all groups revealed fragmented DNA ranging from 200 bp to 3000 bp. These fragmented DNAs were then subjected to IP procedure. Enrichment process of the IP was successfully proven through control DNA amplification and digestion by NcoI by comparing the band intensity before and after IP. Amplification of seven ck promoter CpG island regions after IP revealed most PCR products at expected sizes, but there were inconsistency in band intensity within CpG regions of similar group and among the groups. Out of these seven regions, ckα-2ndCpG-2, ckβ-3rdCpG-4 and ckα-4thCpG-7 regions showed higher level of methylation status after budesonide drug treatment, while ckβ-1stCpG-1 and ckβ-3rdCpG-4 regions showed lower level of methylation status after 5-azacytidine drug treatment. However, this analysis warrants further investigation, since only seven instead of fourteen CpG regions of ckα and ckβ promoter were analysed. Analysis of all fourteen ckα and ckβ promoter CpG island regions could give clearer information on both ckα and ckβ promoter CpG island methylation status after the treatment of epigenetic drugs.